2020
DOI: 10.2147/ott.s237580
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA CRNDE Promotes Colorectal Carcinoma Cell Progression and Paclitaxel Resistance by Regulating miR-126-5p/ATAD2 Axis</p>

Abstract: Background: Long non-coding RNA colorectal neoplasia differentially expressed (lncRNA CRNDE) and microRNA-126-5p (miR-126-5p) were reported to be related to the development of colorectal carcinoma (CRC). However, the detailed mechanism of CRNDE and miR-126-5p is not fully understood. The purpose of this research was to explore their roles and molecular mechanism in CRC. Methods: Quantitative real-time polymerase chain reaction was performed to detect the transcription levels of genes. Paclitaxel (PTX) was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Down-regulated in MYCN-amplified NB [22,29] and in chemoresistant NB [13] Down-regulated in cervical [30], breast [31,32] gastric [32,33], and lung [34] cancer, osteosarcoma [35], and mesothelioma [36] miR-19b 7.75 Up-regulated in chemoresistant NB [37] Down-regulated in breast [38] and colon [39] cancer and leukemia [40] miR-26b 47.87 Not evaluated Down-regulated in chemoresistant colorectal [41], gastric [42], laryngeal [43], and hepatocellular carcinoma [44,45] cancer and in glioma [46] [48], breast [49], and gastric cancer [50] miR-29c 9.27 Not evaluated Down-regulated in ovarian [51], endometrial [52], gastric [53], and small cell lung [54] cancer, glioma [55,56], and leukemia [57,58] miR-34c 7.49 Not evaluated Down-regulated in colon [59], gastric [60,61], and ovarian [62,63] cancer, and osteosarcoma [64] miR-126a 9.66 Not evaluated Down-regulated in colorectal [65] and breast cancer [66] and in renal cell carcinoma [67] miR-218 12.30…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Down-regulated in MYCN-amplified NB [22,29] and in chemoresistant NB [13] Down-regulated in cervical [30], breast [31,32] gastric [32,33], and lung [34] cancer, osteosarcoma [35], and mesothelioma [36] miR-19b 7.75 Up-regulated in chemoresistant NB [37] Down-regulated in breast [38] and colon [39] cancer and leukemia [40] miR-26b 47.87 Not evaluated Down-regulated in chemoresistant colorectal [41], gastric [42], laryngeal [43], and hepatocellular carcinoma [44,45] cancer and in glioma [46] [48], breast [49], and gastric cancer [50] miR-29c 9.27 Not evaluated Down-regulated in ovarian [51], endometrial [52], gastric [53], and small cell lung [54] cancer, glioma [55,56], and leukemia [57,58] miR-34c 7.49 Not evaluated Down-regulated in colon [59], gastric [60,61], and ovarian [62,63] cancer, and osteosarcoma [64] miR-126a 9.66 Not evaluated Down-regulated in colorectal [65] and breast cancer [66] and in renal cell carcinoma [67] miR-218 12.30…”
Section: Resultsmentioning
confidence: 99%
“…In detail, miR-27b and miR-16-1 expression levels were found to be reduced by 33.1 and 23.5 fold, respectively, and miR-218 expression was diminished by 9.09 fold, while miR-15a, miR-126, and miR-19b were down-regulated (slightly, but significantly) by 2.8, 2.7, and 1.73 fold, respectively. [59], gastric [60,61], and ovarian [62,63] cancer, and osteosarcoma [64] miR-126a 9.66 Not evaluated Down-regulated in colorectal [65] and breast cancer [66] and in renal cell carcinoma [67] miR-218 12.30 Up-regulated in MYCN-amplified and in metastatic NB [68][69][70] Down-regulated in glioma cells [71], colorectal [72], gallbladder [73], bladder [74], and lung cancer [75,76] miR-338 15.99 Down-regulated in resistant NB [77,78] Down-regulated in esophageal squamous carcinoma cells [79] miR-497 6.92…”
Section: Resultsmentioning
confidence: 99%
“…Further evidence showed that miR-126-5p is negatively correlated with LINC00665. It has been demonstrated that miR-126-5p plays a role as a tumor suppressor in many cancers [ 32 , 33 ], including CRC. Additionally, to confirm that LINC00665 competitively binds to miR-126-5p, related functional experiments were used.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, we speculated that miR-126-5p may be a pathogenic miRNA existed in OA progression. On the other hand, miR-126-5p is revealed to act as the downstream targets of varied lncRNAs, such as lncRNA CRNDE [33], lncRNA HOTAIR [34], and lncRNA TMPO-AS1 [35].…”
Section: Discussionmentioning
confidence: 99%